Jean-Jacques Rousseau's Dramatization of the Self - Domines Veliki, Martina (Array, 2009)
Though not the first writer of autobiography in the European literary tradition, Jean-Jacques Rousseau ushered in a new model of secular autobiography in a desperate search for 'a stabilizing wholeness for the self' (Anderson). Instead of turning to God as the ultimate arbiter of truth he turned to himself and to his audience. All the works in his autobiographical trilogy violate the conventions of the autobiographical genre and by the same token relate to the tradition of the genre (de Man). In The Confessions, the first work in his trilogy, the question of deceit places itself at the heart of his project and the reader is entangled in the interplay of truth and lie. The Dialogues plays with the multiplications of 'the self' and openly shows the author's fictionalizations of 'the self', warning us against any facile assumption of transparent autobiographical writing. The last work in the trilogy, The Reveries of A Solitary Walker, shows Rousseau still asking the initial question 'What am I?', without any possibility of achieving a sastisfying answer. This dead end of his autobiographical project happens paradoxically because Rousseau has to use language to express his self and he remains irremediably split in and by language. His autobiographical texts aspire to truth but truth remains secondary to staging the drama of the self. The textual 'I' seeks out excuses to perform itself and the text generates guilt in order to justify the excuse (de Man). Autobiography remains a privileged form for Rousseau because it offers the possibility of fixing oneself through writing, the possibility later explored by the writers of the Romantic period.